The Influence of Customer Value and Experience on Loyalty with Satisfaction as Intervening Variable in BPRS Kedung Arto - Wiyono, Sakti; Tjahjaningsih, Endang (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The objective of this paper is to analyze the influence of Customer Value and Customer Experience on Customer Loyalty, with Satisfaction positioned as a mediating variable among Islamic banking customers. This research is motivated by the recognized significance of customer loyalty in the highly competitive Islamic financial industry. Quantitative methods were applied, and data were collected through a questionnaire-based survey. The data were then analyzed through multiple linear regression and the Sobel test to evaluate the mediating role of Satisfaction. The results of this work show that Customer Value and Experience significantly and positively influence Satisfaction, with Experience emerging as the more dominant driver (β= 0.572). Furthermore, a strong direct effect of Customer Value, Experience, and Satisfaction on Loyalty was found. The mediating role of Satisfaction as a partial mediator in the relationships between both Customer Value and Experience toward Loyalty was confirmed. As a managerial implication, it is recommended that Islamic bank management enhance holistic customer experience management and optimize product value propositions to strengthen customer loyalty by fostering higher satisfaction levels.